Adaptive Laboratory Evolution of Eubacterium limosum ATCC 8486 on Carbon Monoxide - Kang, Seulgi; Song, Yoseb; Jin, Sangrak; Shin, Jongoh; Bae, Jiyun; Kim, Dong Rip; Lee, Jung-Kul; Kim, Sun Chang; Cho, Suhyung; Cho, Byung-Kwan (Frontiers in Microbiology, 2020)
Acetogens are naturally capable of metabolizing carbon monoxide (CO), a component of synthesis gas (syngas), for autotrophic growth in order to produce biomass and metabolites such as acetyl-CoA via the Wood–Ljungdahl pathway. However, the autotrophic growth of acetogens is often inhibited by the presence of high CO concentrations because of CO toxicity, thus limiting their biosynthetic potential for industrial applications. Herein, we implemented adaptive laboratory evolution for growth improvement of Eubacterium limosum ATCC 8486 under high CO conditions. The strain evolved under syngas conditions with 44% CO over 150 generations, resulting in a significant increased optical density (600 nm) and growth rate by 2.14 and 1.44 folds, respectively. In addition, the evolved populations were capable of proliferating under CO concentrations as high as 80%. These results suggest that cell growth is enhanced as beneficial mutations are selected and accumulated, and the metabolism is altered to facilitate the enhanced phenotype. To identify the causal mutations related to growth improvement under high CO concentrations, we performed whole genome resequencing of each population at 50-generation intervals. Interestingly, we found key mutations in CO dehydrogenase/acetyl-CoA synthase (CODH/ACS) complex coding genes, acsA and cooC. To characterize the mutational effects on growth under CO, we isolated single clones and confirmed that the growth rate and CO tolerance level of the single clone were comparable to those of the evolved populations and wild type strain under CO conditions. Furthermore, the evolved strain produced 1.34 folds target metabolite acetoin when compared to the parental strain while introducing the biosynthetic pathway coding genes to the strains. Consequently, this study demonstrates that the mutations in the CODH/ACS complex affect autotrophic growth enhancement in the presence of CO as well as the CO tolerance of E. limosum ATCC 8486.